IMPACT ASSESSMENT OF KNOWLEDGE MANAGEMENT, HRD PRACTICES FOR ORGANIZATIONAL PERFORMANCE IN STEEL INDUSTRY IN INDIA - Dash, Srinibash; Sekhar Rath, Sudhanshu; Pati, Uma Charan (International Journal of Psychosocial Rehabilitation, 2020)
The study will access the HRD Practices, knowledge management for organizational performance. In today every firm used its allocated recourses in such a way that it will create a value of the firms without incurring any loss. In this regard very recently, the firm’s strategic section would like to investigate the real role of human resources in enhancing the real value for the organizations. Hence, in the recent techno world Knowledge management (KM) has emerged as an important leading attribute that can help to enrich the organization's cultural value for developing the organizational performance by use of right knowledge which can help to minimize the loss of valuable knowledge when employees leave. Human Resource Development (HRD) Climate is the real attributes of the organization which pushes positively to increase the real knowledge management. Further, knowledge management is being treated as a major parameter for the real growth of organizational performance. In this regard, the study will be focused to identify the HRD practices being implemented in the Steel industry of Odisha and evaluate the impact of HRD practices on organizational performance in the Steel industry. Also, the study evaluates the mediating effect of knowledge management between HRD practices and organizational performance in the Steel industry through Structural equation modeling. In the same line, to carry out this study, two important hypotheses have been developed to prove the effectiveness of knowledge management and HRD practices for organizational performance.